Case Report: Suppression of Harem Stallion Behavior and Fertility Following Anti-Gonadotropin-Releasing Hormone Vaccination of a Captive Wild Przewalski's Horse (Equus ferus przewalskii) - Ponthier, Jérôme; Rigaux, Goulven; Parrilla-Hernandez, Sonia; Egyptien, Sophie; Gatez, Carine; Carrasco Leroy, Carla; Deleuze, Stéfan (Frontiers in Veterinary Science, 2020)
This report describes an option to modulate the testicular function of wild horses and field methods to assess it. Non-surgical castration of a captive wild Przewalski's stallion with anti-gonadotropin-releasing hormone (GnRH) immunization was performed by sub-cutaneous injection of two doses of 450 μg (3 ml) of GnRH conjugated to diphtheria toxin, further repeated every 6 months. Semen quality was assessed after collection by electro-ejaculation under general anesthesia. Endocrine and behavioral consequences were studied during a 2-year follow-up period. The procedure of electro-ejaculation was safe and effective to collect spermatozoa. Motility was low but was improved by a significant dilution of sample (1v/4v−1v/5v) after collection. Immuno-neutering resulted in a decrease of the total spermatozoa number and motility 1 month after primary vaccination. However, infertility could not yet be guaranteed. Six months post-vaccination, serum testosterone concentrations had decreased and the treated stallion had lost his harem stallion role. Moreover, at the same time, the total spermatozoa number was near zero with no motile spermatozoa, and offspring was no longer observed. As a conclusion, electro-ejaculation under general anesthesia is suitable on wild horses to obtain spermatozoa that should be washed or largely diluted before use for artificial insemination (AI) programs. Anti-GnRH immuno-neutering protocol led to a dramatic decrease of spermatozoa number, motility, and testosterone production. This also induced deep changes in the social structure of the band. Such technique could be considered as an alternative to surgical castration in wild horses.